Depression by gender and associated factors among older adults in India: implications for age-friendly policies - Ronak Paul; T. Muhammad; Rashmi Rashmi; Palak Sharma; Shobhit Srivastava; Preeti Pushpalata Zanwar (Scientific Reports, 2023)
Abstract Inspite of implementing policies to control mental health problems, depression remains a severe health concern among older adults in India. We examined self-reported differences in the depression among older men and women in India and examined associated factors for gender differences in depression at the population level. We utilized nationally representative data from the Longitudinal Aging Study in India (LASI) wave I, for years 2017–2019. Our analytical sample comprised of 30,637 older adults ages 60 years and above (14,682 men and 15,655 women). We conducted descriptive statistics and Chi-Square tests followed by binary logistic regression and multivariate decomposition analyses to examine our study objectives. Depression was reported in − 7.4% (95% CI 7.0, 7.8) of older men and 9.5% (CI 9.1, 10.0) of older women. Poor self-rated health, multimorbidity status, physical activity, difficulty in activities of daily living (ADL) and instrumental ADL (IADL) were the significant health-related factors associated with depression among older men and women. Not being satisfied with one’s life, not being satisfied with their present living arrangement, receiving any type of ill-treatment, and being widowed were the significant factors associated with depression among older men and women. We found gender disparity in self-reported depression. Marital status contributed-to 36.7% of the gender gap in depression among older adults. Additionally, ADL and IADL difficulties among men and women contributed to 17.6% and 34.0%, gender gap, self-rated health contributed to 18.8% gap, whereas not having equal social participation (4.4%) and not satisfied in present living arrangements (8.1%) were other factors that contributed to gender gap for depression in India. Depression is a critical and persistent public health problem among—older females in India. Our findings provide a broader framework for policymakers and health practitioners to focus on gender-specific strategies to mitigate this highly emergent problem.